653. DOES MIE REDUCE PULMONARY COMPLICATIONS IN A REAL-WORLD SCENARIO?. (24th September 2022) - Gopinath, Srinivas Kodaganur; Jiwnani, Sabita; Karimundackal, George; Tiwari, Virendrakumar; Niyogi, Devayani; Ranganathan, Priya; Pramesh, CS
Abstract: Pulmonary complications are a common cause of morbidity, and occurs in upto 30% after esophagectomy. Randomised trials have shown significant decrease in pulmonary complications after minimally invasive esophagectomy (MIE). We conducted a study to evaluate whether this was true in a real-world scenario. We performed a retrospective analysis of a prospectively maintained database of patients undergoing esophagectomy. Data of consecutive patients undergoing MIE or open Mc-keown transthoracic esophagectomy (OE) between 2013 and 2021 were included. Categorical variables were compared by Pearson's Χ2 test or Fisher's exact test. Multivariate logistic regression analysis was performed to analyse the relation between pulmonary complications and potential related factors to identify independent predictors of pulmonary complications. A total of 1046 patients underwent MIE or OE between 01/01/2013 and 31/12/2021. The mean age was 54.2+/-9.9 y; 413 (39.5%) were smokers; 862 (82.4%) patients underwent neo-adjuvant chemotherapy; 411 patients(41.1%) underwent MIE( 309- VATS, 102- Robotic) while the remaining 635 underwent OE. Overall, 354(33.8%) patients had pulmonary complications, of which 234(22.4%) were CD 3a and above. Pulmonary complications were reduced by 11.6% (171/635, 26.9% with OE vs 63/411, 15.3% with MIE; p=0.001)(). On multivariate analysis, age > 60y, open surgery, FEV1, 3-field lymphadenectomy and ASA grade(II and III) were found to be significant predictors of pulmonary complications (table 1) Adoption of MIE results in fewer pulmonary complications in the real world; however, the large differences seen in randomised trials may not be replicable in a real-world scenario. Elderly patients, those with low FEV1 values, a higher ASA grade and those who have undergone a 3-field lymphadenectomy may develop significant pulmonary complications in spite of undergoing MIE.